2011
DOI: 10.1186/2047-783x-16-12-557
|View full text |Cite
|
Sign up to set email alerts
|

Elderly people in many respects benefit from interaction with dogs

Abstract: Over the course of evolution, humans and animals have entered into a close relationship. By domesticating animals, humans were able to use them to their own advantage. However, animals should not only be seen as mere providers of material value; in fact, they actually enrich humans' lives on an emotional level. The classic examples for this evolution are dogs: they are considered loyal companions, particularly for children and elderly people. This relationship between humans and animals is the subject of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 13 publications
(14 reference statements)
1
42
0
2
Order By: Relevance
“…Many older adults do not have the opportunities to establish new social contacts, but pets can provide one option for a satisfying emotional relationship (Scheibeck et al 2011). The results of a study done by Krause-Parello (2013) support this premise by finding that attachment to a pet is significantly related to a decreased feeling of loneliness.…”
Section: Loneliness and Isolationmentioning
confidence: 77%
See 1 more Smart Citation
“…Many older adults do not have the opportunities to establish new social contacts, but pets can provide one option for a satisfying emotional relationship (Scheibeck et al 2011). The results of a study done by Krause-Parello (2013) support this premise by finding that attachment to a pet is significantly related to a decreased feeling of loneliness.…”
Section: Loneliness and Isolationmentioning
confidence: 77%
“…For example, a recent study of older adults who presented to their primary care physician found that those owning a pet were 36 % less likely to report loneliness than older adults without pets (Stanley et al 2014). Due in part to the results of these studies, the unique relationship older people share with their dogs as emotional companions has gained growing attention (Scheibeck et al 2011). Contrary to some beliefs, there has been little evidence to suggest that a close relationship with a pet comes at the expense of human relationships.…”
Section: Loneliness and Isolationmentioning
confidence: 96%
“…The owners experienced that dogs could be social facilitators, and they associated their dogs with memories of deceased family members. It was pointed out that, for a person who loves a pet, the animal is a friend and a loyal companion (Scheibeck et al, 2011). A literature review of the association between pet ownership and human health confirmed that companion animals can positively affect human health and enhance their owners' quality of life.…”
Section: International Studiesmentioning
confidence: 99%
“…thereby act as an agent for improving physical activity and change in their lifestyle [2]. Pet walking have improved the children's physical activities; among obese children's [3,4] and elderly [5]. Pet-assisted therapy for hospitalized children's with cancer has alleviated their emotional distress, facilitated their adaptation to the healing process and promoted their well-being [6].…”
Section: Modern Era: Sedentary Lifestylementioning
confidence: 99%